2016
DOI: 10.1002/masy.201400259
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Dispersion and Relaxation in Polymer Blend Based Nanodielectric Film

Abstract: Summary: Polymer nanodielectrics is the exponential growing field of advanced materials sciences. Such flexible materials have recognized their suitability as substrate and insulator in fabrication of microelectronic devices, and also in preparation of ion conducting solid polymer electrolytes. The nanodielectric film consisted of poly(ethylene oxide) and poly(methyl methacrylate) (PEO-PMMA; 75/ 25 wt/wt%) blend with 5 wt% montmorillonite (MMT) clay as nanofiller has been prepared by solution-casting method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…Compared to the SA film, our composite films have a higher ε′ value. This observation is consistent with previous studies in which an increase in ε′ has been noted upon the incorporation of metal oxides into a polymer ( Prabu and Selvasekarapandian, 2012 ; Abdel-Baset et al, 2016 ; Sengwa and Choudhary, 2016 ; Choudhary and Sengwa, 2017 ). The high ε′ value of our composite films is contributed by the even dispersion of LAO NPs in the SA matrix and by the high εʹ value of LAO NPs.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Compared to the SA film, our composite films have a higher ε′ value. This observation is consistent with previous studies in which an increase in ε′ has been noted upon the incorporation of metal oxides into a polymer ( Prabu and Selvasekarapandian, 2012 ; Abdel-Baset et al, 2016 ; Sengwa and Choudhary, 2016 ; Choudhary and Sengwa, 2017 ). The high ε′ value of our composite films is contributed by the even dispersion of LAO NPs in the SA matrix and by the high εʹ value of LAO NPs.…”
Section: Resultssupporting
confidence: 93%
“…The diffraction peaks from LAO NPs are found in the diffraction patterns of all of the film samples. This implies that the structure of the NPs remains unchanged, and that the films are crystalline in nature ( Afzal et al, 2008 ; Ionita et al, 2013 ; Sengwa and Choudhary, 2016 ). When the amount of LAO NPs in a film increases, the peak at 2θ = 13.32° shows a decrease in intensity but an increase in broadness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] Most of the studies have concluded that the nanoclay structures (i.e., the amounts of exfoliated or intercalated and the sizes of tactoids) in the host polymer matrices predominantly rule the useful properties of such hybrid nanocomposites. [1][2][3]6,[8][9][10][11][12][13] So with the consideration of this fact, enormous attempts had been made to achieve better homogeneous dispersion of loaded nanoclay platelets in the PEO matrix by adopting different preparation methods. 5,6,[9][10][11] Furthermore, numerous researches evidenced that the loading of treated-nanoclay in the polymer matrices formed highly successful nanocomposites of improved thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,[9][10][11] In addition to the alterations in chemical and thermomechanical properties of the PNCs, it is also observed that the dielectric and electrical properties of nanoclay loaded polymer matrices are largely affected by the intercalated/exfoliated clay structures. 4,7,12,13,[16][17][18][19][20][21] However, most of the dielectric studies on the clay containing PNCs were performed with externally applied electric field starting from frequency of a few millihertz or hertz and extending up to some megahertz. It is because of the fact that the interfacial polarization largely contributes to the dielectric permittivity in all types of hybrid nanocomposites at lower frequencies which is imperative for exploring their nanodielectric applications in low-frequency device technologies.…”
Section: Introductionmentioning
confidence: 99%